Effect of physicochemical parameters on zooplankton at a freshwater body of Euphrates Basin (Elazig-Turkey) - Bulut, Hilal; Saler, Serap (C M B Assoc, 2019)
In this study zooplankton was determined between June 2015-May 2016 in Keban Reservoir. Also some chemical and physical parameters as water temperature, pH, dissolved oxygen. electrical conductivity and Chlorophyll a were measured in situ, monthly. Total of 40 zooplankton species; 27 Rotifera, 11 Cladocera, 2 Copepoda species were identified in this study. The data of this study were evaluated number of individuals, species richness and species diversity. Maximum, minimum, SD and mean values of water quality parameters were calculated. As a result of Shannon Wiener index analysis of current study, species diversity was found highest in January (H'=2.03) and the least index value was found in May (H'=0.46). Margalef index value recorded in its highest value in January (D=1.07) in the 2nd station and the lowest value in February (D=0.11) in the 1st station.
Keywords: Water quality parameters; Zooplankton; Species diversity; Species richness; Euphrates Basin